2004
DOI: 10.1111/j.1365-2028.2004.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic aspects of sympatric Praomys jacksoni and P. stella in a tropical lowland forest in Kakamega, Kenya

Abstract: Populations of coexisting tropical forest rodents Praomys jacksoni and P. (Hylomyscus) stella were investigated to test whether lower relative densities in regenerating forest compared with mature forest were because of poor health and/or reduced chances for females to breed. Relative frequencies, litter size, mass, length of embryos, presence or absence of ecto-and/ or endoparasites, and liver condition were recorded and analysed. Higher numbers of either species occurred in the mature compared with regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…These can be manifested through their feeding and mobility, resulting in weight loss and reduced growth (Jog & Watve 2005). Heavier animals are infected more significantly by parasites than lighter ones (Waweru & Odanga 2004). However, in the present study individuals with high load of infestation were similar in body weight and size to the non-infected individuals and both sexes have an equal probability to be infested by ectoparasites.…”
Section: Discussioncontrasting
confidence: 54%
“…These can be manifested through their feeding and mobility, resulting in weight loss and reduced growth (Jog & Watve 2005). Heavier animals are infected more significantly by parasites than lighter ones (Waweru & Odanga 2004). However, in the present study individuals with high load of infestation were similar in body weight and size to the non-infected individuals and both sexes have an equal probability to be infested by ectoparasites.…”
Section: Discussioncontrasting
confidence: 54%
“…In the tropics, the abundance of rainfall, fruits and insects are important factors that might act directly or indirectly to initiate breeding activity to ensure that lactation occurs during a period when food abundance is greatest (Nicolas et al 2003). In the rainy season, the abundance of a frugivore-granivore forest specialist, P. delectorum, might increase as a result of an increase in fruit abundance and abundance and quality of the leaf litter on which this species relies (Waweru & Odanga 2004). An additional reason for the growth of P. delectorum populations might be earlier and greater recruitment of young and/or survival during the preceding short rains (Makundi et al 2007).…”
Section: Seasonal and Habitat Variation In Host And Flea Species Compmentioning
confidence: 99%
“…Chapman and Chapman (1999) reported that their capture success doubled in the disturbed forest, while Isabirye-Basuta and Kasenene (1987) found significant differences for Hylomyscus stella but not for Praomys jacksoni. Waweru and Odanga (2004) in the Kakamega Forest found higher abundance in a portion of mature forest when compared to a fragment of regenerating forest (clear felled 15 years before). In all these cases anthropogenic disturbance coincided with logging; as previously stated this is not the case for our study areas, so the fact that we did not observe significant differences could be due the fact that this kind of anthropogenic disturbance does not affect this demographic parametre.…”
Section: Discussionmentioning
confidence: 95%
“…Some factors that may bias results are: (a) traps and baits are species-specific so it is possible that many species are not trapped (Gurnell and Flowerdew 1994;Barnett and Dutton 1995); (b) rare species were represented by one single capture, so probability of capture for these species was very low, hence prone to stochastic variability; in this case the Simpson Index, as it is less sensitive to rare species, might be more indicative (Hair 1980); (c) although we used arboreal traps, our efforts were limited to the first 3 m: to obtain a complete inventary of species one should sample up to the canopy (Delany 1986;Barnett and Dutton 1995). Our list of species is similar to the one obtained by Waweru and Odanga (2004) in the Kakamega Forest except for Colomys goslongi and Rattus rattus which they caught in a fragment of regenerating forest (clear-felled 15 years before) therefore in a different habitat. Our list of species and community structure is also similar to the ones of similar studies in forests of East Africa: Isabyrie-Basuta and Kasenene (1987) and Chapman and Chapman (1999), in the Kibale Forest found that the two forest specialist Praomys jacksoni and Hylomyscus stella, were the most abundant species, followed by Lophuromys flavopunctatus and Mus (Nannomys) minutoides.…”
Section: Discussionmentioning
confidence: 99%